ANALISIS PROSES PRODUKSI BATA RINGAN DENGAN RESPON SURFACE METHODE - Sahril Mashuri Ihsan; Boy Rollastin (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Light brick is a building material that is still quite foreign among the middle to lower society, the composition of light brick building materials is still quite interesting to research. In some previous studies, attempts to find the optimum composition of light brick mixtures used experimental methods that evaluated the influence of a factor in an experiment. The outcome of a production process can be influenced by a variety of factors. In this study was conducted to find the optimum composition of light brick building materials by applying the Response Surface Methode method. Research shows that the proportion of materials that produce the most optimal water absorption is rice husk (8.5%) and foam agent (0.9%), which is able to produce light bricks with an average water absorption of 50.22%.The results of this study also recommend a general equation to predict the absorption of light brick water when using both compositions of the material, namely: Y = 43,206 - 2.119X_1 - 1,228 X_2 - 8,479 x_1^2 – 2,264 x_2^2 - 13.785X_1 X_2 with X_1 and X_2 respectively is the proportion of rice husks and foam agents, respectively.